2018
DOI: 10.1002/jso.25029
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional analyses of the learning curve for single‐incision plus one port laparoscopic surgery for sigmoid colon and upper rectal cancer

Abstract: For experienced CLS surgeons, the learning process reached the plateau period after the 13th case, and technical competence was achieved after the 44th case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Kim et al reported that the learning curve of SPS for sigmoid colon cancer was 61-65 cases according to multidimensional statistical analyses (16). Li et al reported that the experienced MPS surgeons achieved the technical competence after the 44th case of SPS plus one port in patients with sigmoid colon cancer and upper rectal cancer (17). SPS for rectal cancer is technically more challenging and require more cases for proficiency, and we consider this result is likely little of statistical significance.…”
Section: Discussionmentioning
confidence: 88%
“…Kim et al reported that the learning curve of SPS for sigmoid colon cancer was 61-65 cases according to multidimensional statistical analyses (16). Li et al reported that the experienced MPS surgeons achieved the technical competence after the 44th case of SPS plus one port in patients with sigmoid colon cancer and upper rectal cancer (17). SPS for rectal cancer is technically more challenging and require more cases for proficiency, and we consider this result is likely little of statistical significance.…”
Section: Discussionmentioning
confidence: 88%
“…We attempted to perform SILS + 1 since 2012 [ 22 ], after the learning curve was overcome in 2014 [ 24 ]. Between January, 2015 and December 2018, 2257 consecutive colorectal cancer patients received curative laparoscopic surgery (SILS + 1 or CLS) in the Dept.…”
Section: Methodsmentioning
confidence: 99%
“…Surgeries were performed by surgeons who had completed over 200 successful CLS cases and 50 SILS + 1 cases after passing the SILS + 1 learning curve, with regard to our previous study [ 24 ]. Two surgeons participated in the study.…”
Section: Methodsmentioning
confidence: 99%